2022
DOI: 10.1007/s11604-022-01297-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cryoablation for clinical T3a renal cell carcinoma (< 7 cm) with segmental vein involvement or perinephric fat invasion based on preoperative evaluation of high-resolution multidetector computed tomography scan

Abstract: Purpose To retrospectively assess the feasibility, safety, renal function, technique efficacy rate, and survival of patients with clinical T3a renal cell carcinoma (RCC). Materials and methods Sixteen cryoablation sessions were performed in 14 patients (10 men; mean age, 69.8 ± 10.5 years; range, 49–90 years) with 14 clear cell T3a RCCs (mean, 3.3 ± 0.9 cm; range, 1.9–5.2 cm). One patient was on dialysis. Transcatheter arterial embolization was performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, a retrospective study found that larger T1 tumors could benefit from CA as much as T1a tumors, since there was no statistical difference in local recurrence between tumors <3 cm and >3 cm (p =0.15) ( 22 ). A study even suggested the feasibility of CA for T3a RCC for inoperable patients ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a retrospective study found that larger T1 tumors could benefit from CA as much as T1a tumors, since there was no statistical difference in local recurrence between tumors <3 cm and >3 cm (p =0.15) ( 22 ). A study even suggested the feasibility of CA for T3a RCC for inoperable patients ( 23 ).…”
Section: Discussionmentioning
confidence: 99%